Impact and survival strategies of UMKM in cakung sub-district during the covid-19 pandemic - Dwi Listyowati; Sita Dewi; Bertha Elvy Napitupulu (International Journal of Informatics, Economics, Management and Science (IJIEMS), 2023)
UMKM (MSMEs) or Usaha Mikro Kecil dan Menengah (Micro, Small and Medium Enterprises) are productive business units that can be carried out by individuals or business entities in all economic sectors. UMKM have driven Indonesia's economy and development. Through UMKM, new jobs are created, there is an increase in tax revenue, an increase in GDP (Gross Domestic Product) as well as its contribution to exports and the creation of fixed capital/investment. The number of UMKM in Indonesia is 64.19 million, where the composition of micro and small enterprises is very dominant, namely 64.13 million or around 99.92 percent of the total business sector.The covid-19 pandemic has made the economy in the world, including in Indonesia, fall into a crisis. UMKM, which is usually able to survive when hit by an economic crisis, turned out to be the sector that was affected during the pandemic. The difficulties faced by UMKM players during the covid-19 pandemic are declining sales, difficulties with capitalization, obstacles to product distribution and difficulty in obtaining raw materials. During the Covid-19 pandemic, there were restrictions on activities so that UMKM players had to carry out the right strategy to continue to do business in this situation. E-commerce is carried out to continue to serve consumers and also so that the business being managed can survive. In addition to e-commerce, innovating makes business people or business actors, including UMKM,still able to survive during the Covid-19 pandemic. The government provides support incentives for UMKM through the National Economic Recovery (PEN) program in 2020 and continued in 2021.The purpose of this study was to determine the impact of the covid-19 pandemic on the businesses of UMKM Cakung players, and to determine the effect of e-commerce, innovation, government policies on the survival position of UMKM Cakung. The sample of this study was 35 UMKM Cakung players who were randomly selected. Data analysis was carried out descriptively and by regression and correlation. The results showed that the covid-19 pandemic had an impact on the businesses of UMKM Cakung players. E-commerce and innovation partially have no effect on the survival position of UMKM Cakung, but government policies affect the survival position of UMKM Cakung . Simultaneously, e-commerce, innovation and government policies have an influence on the survival position of UMKM Cakung.